Critically ill allogenic HSCT patients in the intensive care unit: a systematic review and meta-analysis of prognostic factors of mortality. (October 2018) - Saillard, Colombe; Darmon, Michael; Bisbal, Magali; Sannini, Antoine; Chow-Chine, Laurent; Faucher, Marion; Lengline, Etienne; Vey, Norbert; Blaise, Didier; Azoulay, Elie; Mokart, Djamel
Abstract Outcome of patients undergoing allogenic hematopoietic stem cell transplantation (allo-HSCT) has improved. To investigate if this improvement can be transposed to the ICU setting, we conducted a systematic review and meta-analysis to assess short-term mortality of critically ill allo-HSCT patients admitted to the ICU and to identify prognostic factors of mortality. Public-domain electronic databases, including Medline via PubMed and the Cochrane Library were searched. All full-text articles written-English studies published from 2006 to 2016, including allo-HSCT adults transferred to the ICU were included. Eighteen studies were selected, including 2342 patients. Overall estimated ICU mortality was 51.7%. Prognostic factors associated with an increased ICU mortality were mechanical ventilation (OR = 12.2, 95% CI = 6.2–23.7), vasopressors (OR = 6.3, 95% CI = 3.6–11.1), renal replacement therapy (OR = 4.2, 95% CI = 2.8–6.2), ICU admission for acute respiratory failure (OR = 2.2, 95% CI = 1.1–4.4), acute kidney injury (OR = 2.2, 95% CI = 1.3–4), and acute graft-versus-host disease (OR = 1.6, 95% CI = 1.1–2.3). Factors associated with an increased ICU survival were a single-organ failure (OR = 0.2, 95% CI = 0.1–0.4), neurological failure (OR = 0.4, 95% CI = 0.2–0.8), and reduced-intensity conditioning regimens (OR = 0.7, 95% CI = 0.5–0.9). Septic shock, underlying malignancy, disease status, donor, and graft source did not impact prognosis. Outcome has improved, supporting the usefulness of ICU management. Organ failures at ICU admission, organ support requirement, and GVHD are the main prognostic factors.